2014
DOI: 10.4236/ijg.2014.53031
|View full text |Cite
|
Sign up to set email alerts
|

An Interpretation of Structures from the Aeromagnetic Field over a Region in the Nigerian Younger Granite Province

Abstract: An interpretation of high resolution aeromagnetic data was carried out to provide new information about the study area. Located between latitude 10˚30'N and 11˚00'N and longitude 8˚30'E and 9˚00'E, the interpretation revealed previously unknown folds and magnetic anomaly with a signature that is similar to those associated with ring complexes in the study area but without the surface manifestation that is associated with the complexes. Qualitatively interpreted as unexposed ring complex, the magnetic anomaly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…Following Oladunjoye et al (2016), the thermal effects of the emplacement of the basement rocks whose epeirogenesis is associated with the Pan African events may be possible cause of the curvilinear lineament observed in northern part of the study area. Finally, the lineament trends inferred in this study are consistent with the trends inferred from previous studies in the northern Nigerian basement complex (Olasehinde et al, 1990;Raimi et al, 2014;Salau et al, 2016).…”
Section: First Vertical Derivative Results (Fvd)supporting
confidence: 92%
“…Following Oladunjoye et al (2016), the thermal effects of the emplacement of the basement rocks whose epeirogenesis is associated with the Pan African events may be possible cause of the curvilinear lineament observed in northern part of the study area. Finally, the lineament trends inferred in this study are consistent with the trends inferred from previous studies in the northern Nigerian basement complex (Olasehinde et al, 1990;Raimi et al, 2014;Salau et al, 2016).…”
Section: First Vertical Derivative Results (Fvd)supporting
confidence: 92%
“…Some anomalies with the same feature with the anomalies of the ring complexes were also revealed (indicated with question marks within white boxes) but without an associated surface manifestation (outcrop). These anomalies are believed to be intrusions, probably ring complexes without surface exposures, similar to that suggested by Ajakaiye [78] in the north eastern part of the province, Raimi [79] within the Ririwai sheet and by Mantovani, Dutra and Marangoni, Dutra, Louro and Mantovani in central Brazil [80][81][82][83]. The pattern/position of the unexposed ring complex and the approximate thickness of overburden covering it were clearly displayed on the 3D-Euler Deconvolution map.…”
Section: Discussion and Resultssupporting
confidence: 71%
“…The lineament density map and the rose diagram of the study area are shown in Figure 7. There is consistency in the lineament hereby inferred and the previously inferred lineaments in the region [1,11,12].…”
Section: Lineament Study Of the Study Areasupporting
confidence: 85%